Tripartite Evolutionary Game Analysis on Selection Behavior of Trans-Regional Hospitals and Patients in Telemedicine System - Yuxuan Gao; Yueping Du; Bingzhen Sun; Rui Wang; Chaoying Jiang (International Journal of Computational Intelligence Systems, 2017)
This study applies the game theory to the discussion and analysis of trans-regional Telemedicine System, builds the game model of the selection strategies of trans-regional hospitals and patients and analyzes evolving paths, equilibrium states and influencing factors of the three parties. It is derived that medical insurance reimbursement proportion of specialized hospitals, government support for general hospitals and medical expenses in specialized hospitals, operating costs of general hospitals are the influential factors in the Telemedicine System. Finally, a numerical stimulation is conducted with Matlapb based on the data from China Health and Family Planning Statistical Yearbook 2015.